2022
DOI: 10.3389/fmicb.2021.735494
|View full text |Cite
|
Sign up to set email alerts
|

Methicillin- and Vancomycin-Resistant Staphylococcus aureus From Humans and Ready-To-Eat Meat: Characterization of Antimicrobial Resistance and Biofilm Formation Ability

Abstract: Methicillin-resistant and vancomycin-resistant Staphylococcus aureus (MRSA and VRSA) are zoonotic life-threatening pathogens, and their presence in food raises a public health concern. Yet, scarce data are available regarding MRSA and VRSA in both ready-to-eat (RTE) meat and food handlers. This study was undertaken to determine the frequency, antimicrobial resistance, and biofilm-forming ability of MRSA and VRSA isolated from RTE meat (shawarma and burger) and humans (food handlers, and hospitalized patients) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 74 publications
0
23
0
Order By: Relevance
“…Our ndings are compatible with the prior studies that identi ed the icaAD genes are su cient for strong bio lm formation (Arciola et al 2001;Wang et al 2018). However, other authors observed a lower production of icaAD in comparison to the icaADBC expressed simultaneously (Chen et al 2020;Saber et al 2022). This divergence can be explained because of the type of sources that the isolates were obtained from and the exposure to external conditions, such as temperature, pH variation, or other substances that promote the bio lm formation level (Miao et al 2019).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Our ndings are compatible with the prior studies that identi ed the icaAD genes are su cient for strong bio lm formation (Arciola et al 2001;Wang et al 2018). However, other authors observed a lower production of icaAD in comparison to the icaADBC expressed simultaneously (Chen et al 2020;Saber et al 2022). This divergence can be explained because of the type of sources that the isolates were obtained from and the exposure to external conditions, such as temperature, pH variation, or other substances that promote the bio lm formation level (Miao et al 2019).…”
Section: Discussionmentioning
confidence: 80%
“…on several surfaces in kitchen environments, such as knives, sinks, raw meat cutting boards and baking worktops are associated with food handlers carrying S. aureus in cavities nasal and hands (Benjelloun Touimi et al 2020). On the other hand, Staphylococcal bio lm represents one of the greatest risks to food security, since the production of this virulence factor is a risk to the persistence of S. aureus in the kitchen environment, increasing the potential exposure to food and utensils and equipment used (Saber et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, it was observed that S. aureus was isolated in half of the samples of nasal cavities and underside of nails from food handlers. According to Castro et al, 15 Ahmed, 25 and Saber et al 26 the presence of S. aureus in the hands and/or noses of food handlers was of 30%, 25%, and 30%, respectively.…”
Section: Discussionmentioning
confidence: 96%
“…Primer pairs were designed to allow partial amplification of conserved regions in nuc , mec A, and vancomycin-resistance gene variants A and B ( van A/B). The nuc gene encodes for a thermonuclease specific for S. aureus [ 21 ]; mec A encodes for penicillin-binding protein 2 that is responsible for methicillin resistance [ 22 ], and van A/B encodes for vancomycin-resistance determinants type A and B [ 23 ]. Different sequences of the target genes were downloaded from the National Center for Biotechnology Information (NCBI); the list of accession numbers of the used sequences is provided in Table S1 .…”
Section: Methodsmentioning
confidence: 99%